2017
DOI: 10.20517/2394-4722.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in tumor progression: focus on A2B receptor as potential therapeutic target

Abstract: Adenosine receptors are a family of G-coupled receptors which mediate the antiinflammatory and immune-suppressive effects of adenosine in a damaged tissue. A large number of evidence indicate that the accumulation of adenosine under hypoxic conditions favors tumor progression, helping cancer cells to evade immune responses. Tumor cells and/ or lymphoid and myeloid cells can express the adenosine-generating enzyme CD73 and/or A 2A receptor, which in turn strongly suppresses an effective T-cell-mediated response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 117 publications
(190 reference statements)
0
16
0
Order By: Relevance
“…Numerous pre-clinical studies have demonstrated that adenosinergic pathway-targeted therapies can significantly reduce tumor growth and metastasis, improving the T-cell-mediated anti-tumor response [ 48 52 ] and synergize with antibodies anti-PD1 and anti-CTLA4 [ 53 56 ], establishing the bases for ongoing clinical trials [NCT02503774 and NCT02655822]. In this study, we found that the activity of sCD73 determined in the serum before treatment with nivolumab is inversely associated with objective response to nivolumab, leading us to suggest this marker as possible candidate to discriminate responders to non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pre-clinical studies have demonstrated that adenosinergic pathway-targeted therapies can significantly reduce tumor growth and metastasis, improving the T-cell-mediated anti-tumor response [ 48 52 ] and synergize with antibodies anti-PD1 and anti-CTLA4 [ 53 56 ], establishing the bases for ongoing clinical trials [NCT02503774 and NCT02655822]. In this study, we found that the activity of sCD73 determined in the serum before treatment with nivolumab is inversely associated with objective response to nivolumab, leading us to suggest this marker as possible candidate to discriminate responders to non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine was demonstrated to promote VEGF production in rat myocardial myoblasts [97] and in macrophages from C57BL/6 mice [98] It has been demonstrated that AR stimulation could increase VEGF production five-fold in tumor-associated CD45 + immune cells, an effect that is not observed in CD45 + cells from A 2B AR KO mice [96] The A 2B AR induces production of VEGF [23,96,99] and interleukin (IL)-8 in human melanoma cells [46], which are essential for tumor angiogenesis. Bay60-6583, a selective A 2B AR agonist, was demonstrated to induce in tumor expression of VEGF-A [100]. A 2B AR inhibition by a selective antagonist PSB-1115 21 significantly decreased tumor growth by blocking angiogenesis and increasing T cells numbers within the tumor microenvironment.…”
Section: A2bar and Angiogenesismentioning
confidence: 99%
“…DPP4 inhibitor vildagliptin has been reported to suppress lung cancer growth via a macrophage-mediated mechanism [110]. Considering the increased adenosine concentration and increased A 2B AR expression in the tumor microenvironment [17,31,100] together with the high expression levels of both A 2B AR and DPP4 in macrophages and dendritic cells, growing evidence suggests a critical role of A 2B AR together with CD39 and CD73 in modulating cancer progression at least in part via immune suppression. Furthermore, DPP4 physically associates with adenosine deaminase, which controls adenosine concentration and binds to the A 2B AR.…”
Section: A2bar and Immunitymentioning
confidence: 99%
“…From the therapeutic perspective, several adenosine receptor agonists and antagonists, as well as adenosine synthesis inhibitors, are under development for clinical use. 38,39 A 2B agonists are being developed to target cardiovascular disease 14 ; whereas, A 2B antagonists and CD73 inhibitors are being developed to target angiogenesis in cancer/tumors, 40,41 renal fibrosis, pulmonary fibrosis associated with chronic obstructive pulmonary disease, pulmonary hypertension, and dermal fibrosis. As adenosine can have both beneficial and deleterious effects, the challenge going forward is to design drugs that maximize efficacy and minimize deleterious side effects.…”
Section: Hypertensionmentioning
confidence: 99%